The grounds of complaining about the times in the literature of the Seljuk era - قهرمان شیری (تاریخ ادبیات, 2010)
A major part of the public dissatisfaction in the Seljuk era, which is reflected in the complaints of poets about the conditions of life and times, is directly related to the government and politics. In this period, the administration of major parts of the country is in the hands of rulers who have not reached the necessary maturity in terms of age and experience and do not have enough nobility in terms of education and experience, and a group of ignorant and unqualified people have also surrounded the government and its institutions, and all these factors have narrowed the field for the owners of thought and art. When poets and writers evaluate things with their visions of the ideal government and the images they have of the past, they completely lose their hopes for the improvement of the society and cry out in dissatisfaction. Other reasons for this discontent and criticism of the times should be sought in factors such as the diversity of thought, culture and art, and the activity of various religious sects, and the abundance of poets and the breadth of their geographic presence and the diversity of individual styles that both governments and poets have freedom of action and regional independence because the plurality of opinions and tastes and, accordingly, the existence of freedom of choice in society and the possibility of leaving unwanted courts and turning to desirable ones by poets, give them an open and daring attitude. It is for this reason that the most complaints and grievances about times have been made during this period.